IMPLEMENTASI E-OFFICE DALAM MENGATASI PENYEBARAN COVID-19 DI DINAS KOMUNIKASI, INFORMATIKA,PERSANDIAN DAN STATISTIK KABUPATEN SUMEDANG - Teddy Marliady Nurwan; Cucu Warlina; Gita Elfariani; Glendy Ilham Maulidian; Muhammad Ridwan; Nadya Mutia Shofa; Putri Supriatriningsih (JRPA - Journal of Regional Public Administration, 2021)
The study aims to find out how the implementation of the E-Office program, to know the factors against the implementation of the E-Office program, to know efforts to overcome the program implementation obstacles E-Office program by Dinas Komunikasi, Informatika, Persandian, dan Statistik Kabupaten Sumedang. The method used in the compilation of this assessment is a qualitative (natural setting) method with a descriptive type. The identification was taken by the purposive sampling technique, which is the calculated ampel of the data source technique to fit the criteria for the under-targeted phenomena. It’s either a source of data or an informant are The Heads Of The Information Department, Telecommunications Section Chief, and Program Staff. As for the data-collection techniques that are done are the literature and field studies of observation, interviews and documentation. Whereas data processing procedures in this assessment include reduction of data, display data, data triangulation, and a withdrawal of conclusions or verification. Based on analysis and discussion, researchers can conclude that the implementation of the E-Office program in composting Covid-19 by Dinas Komunikasi, Informatika, Persandian, dan Statistik Kabupaten Sumedang has been well carried out, that the E-Office application is very useful because it can help ASN employees become easier and faster in accordance with the policies based on 2020 vice President No.63. The obstacles included in the study are, among other things, a weak internet access network, a user's ability to understand technologies. Whereas efforts to overcome these obstacles include: both in-person socialization and the use of electronic media to increase user understanding of the E-Office application